Insights into circular RNA biology. Issue 8 (3rd August 2017) - Ebbesen, Karoline K.; Hansen, Thomas B.; Kjems, Jørgen
ABSTRACT: Circular RNAs (circRNAs) are a novel class of non-coding RNA characterized by a covalently closed-loop structure generated through a special type of alternative splicing termed backsplicing. CircRNAs are emerging as a heterogeneous class of molecules involved in modulating gene expression by regulation of transcription, protein and miRNA functions. CircRNA expression is cell type and tissue specific and can be largely independent of the expression level of the linear host gene, indicating that regulation of expression might be an important aspect with regard to control of circRNA function. In this review, a brief introduction to the characteristics that define a circRNA will be given followed by a discussion of putative biogenesis pathways and modulators of circRNA expression as well as of the stage at which circRNA formation takes place. A brief summary of circRNA functions will also be provided and lastly, an outlook with a focus on unanswered questions regarding circRNA biology will be included.